1998
DOI: 10.1136/adc.79.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Parental and professional perception of need for emergency admission to hospital: prospective questionnaire based study

Abstract: Aim-To compare views of parents, consultants, and general practitioners on severity of acute illness and need for admission, and to explore views on alternative services. Method-Prospective questionnaire based study of 887 consecutive emergency paediatric admissions over two separate three week periods in summer and winter of five Yorkshire hospitals, combined with a further questionnaire on a subsample. Outcome measures-Parental scores of need for admission and parent and consultant illness severity scores ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 11 publications
(5 reference statements)
2
25
0
Order By: Relevance
“…30,31 Admission rates may be higher from localities with easy access to hospital or vary with clinical and parental thresholds for admission and organization of out of hours primary care services. 32 The rate of emergency hospital admission for respiratory infections in children has increased over the past decade in the United Kingdom. 31 The majority were shortstay admissions, 33,34 suggesting that these were for minor illness episodes that could have been managed in the community.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…30,31 Admission rates may be higher from localities with easy access to hospital or vary with clinical and parental thresholds for admission and organization of out of hours primary care services. 32 The rate of emergency hospital admission for respiratory infections in children has increased over the past decade in the United Kingdom. 31 The majority were shortstay admissions, 33,34 suggesting that these were for minor illness episodes that could have been managed in the community.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Much of the literature focuses on the issue of perceived illness threat, which is known to vary with diagnosis, the child's age, and the parent's perception of general health threat, previous experience of illness, and experience as a parent [13]. Kai's study [10] of parents of preschool children cited cough and fever as two specific symptoms that provoked anxiety that their child would be irretrievably harmed, and a recent hospital-based study from the UK reported substantial differences between parental and physician assessment of illness severity on hospital admission [14]. Our findings simply emphasize the clinical importance of recognizing the contextual factors, including the emotional context, of parent assessment of clinical severity of childhood illness.…”
Section: Discussionmentioning
confidence: 95%
“…Please tick a box for each item (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) that best suits your child over the last 24 hours. The time period to which the chart referred was either 8 hours (for the first 48 hours) or 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…To assess how representative these data might be, we compared frequencies of diagnoses with those in data sets collected during a BPA/RCPCH study in five Yorkshire hospitals,2 3 and in four South of England hospitals during an unpublished study carried out for the National Casemix Office by the BPA in 1995. In addition, we used published epidemiological reports together with data provided by the Public Health Laboratory Service (PHLS) and Department of Health Hospital Episode Statistics (HES) for England.…”
Section: Methodsmentioning
confidence: 99%